Predicting and simulating future land use pattern : a case study of Seremban district - Shamsuddin, Shamsaini; Yaakup, Ahris (Fakulti Alam Bina, UTM, 2007)
As long as rapid urbanization which is a result of natural population growth and rural urban migration due to push and pull factors of social and economic conditions as well as the moving of urban populations from major city centres to urban fringe areas due to changing lifestyle which emphasized on spacious and more comfortable and environmentally friendly living environment continue to happen; towns and cities will continue to grow and expand to accommodate the growing and complex demand of the people. Experiences have shown that rapid and uncontrolled expansion of towns and cities has led to amongst others the deterioration in the quality of urban environment and sprawling of urban development onto prime agricultural and forest areas as well as cities starting to lose their identity. In order to avoid such phenomena continuing to happen, particularly in the Kuala Lumpur Conurbation Area, towns and cities need to be properly planned and managed so that their growth or expansion can be controlled and managed in a sustainable manner. One of the strategies adopted to curb sprawling development is through the delineation of urban growth or development limits (UGL). This means that the limit of towns and cities need to be studied and identified, so that urban development can be directed to areas that are identified and specified suitable for such development. One of the main tasks in the process of delineating UGL has been included as an important task in the preparation of development plans. With such policy a research study is now being carried out to develop a spatial modelling framework towards delineating UGL through the application and integration of spatial technologies and this will be a basis or framework for land use planners, managers and policy makers to formulate urban land use policies and monitor urban land use development. One of the main analysis involve in the process of performing this task is to understand past urban land development trend and to predict and identify future urban growth areas of the selected study area. This paper highlights the integration of statistical modeling technique via binary logistic regression analysis with GIS technology in understanding and predicting urban growth pattern and area as applied to District of Seremban, Negeri Sembilan. The result shows that urban land use pattern in the study area within the study period are significantly related to more than half of the predictors used in the analysis.